The Relationship Between Type and Position of Fungal Infection with Age and Gender - Fanosh, Mohammed Hessiun; Eljamay, Salwa Muftah; Elzer, Ashraf Saad; Alkirbal, Hamdi Abdulbasit (CV. Literasi Indonesia, 2024)
Dermatophytosis is a superficial fungal infection caused by filamentous fungi that attack the keratinized tissue. Aimed to: the find out relationship between type and position of fungal infection with age and gender. Material and Methods: This cross-sectional survey study was carried out at the dermatology department, from August 2021 to July 2023. Results: The ages most affected by fungi were between 17 and 32 years old at 60%, followed by the oldest age over 35 years old. The females were the most infected with fungi, 93 out of 155. As for the type of infection, yeast was the highest, especially in 60 women. hyphae 28 and spores 8 where males were less infectious, the relationship between gender and fungal position, because p-value < 0.05, As for the type of fungus and its existence, it has nothing to do with gender because p-value > 0.05, it has nothing to do with gender because p-value > 0.05, and the relationship between age and presence of fungal infection, because p-value < 0.05, the type of fungus and position of fungal infection, it has nothing to do with age because p-value > 0.05. Conclusion: females are more likely to be infected with fungi, whether they are by infection type or location, and the most infected ages are between 17 and 32 years old. The study also showed that the place of infection in nails was found in males and there was no infection in females.